Cost-effectiveness analysis of hearing screening program for primary school children in southern Iran, Shiraz - Mohammad Faramarzi; Sara Babakhani fard; Mohsen Bayati; Fatemeh Jafarlou; Mohammadreza Parhizgar; Mehdi Rezaee; Khosro Keshavarz (BMC, 2022)
Abstract Background Hearing loss is the second most common chronic disease, the diagnosis and treatment of which can be faster through screening. In addition, early interventions will save significant costs for the education and health systems. Therefore, the present study aimed to evaluate the cost-effectiveness of hearing screening for primary school children in Shiraz. Methods This cross-sectional economic evaluation of cost-effectiveness was conducted from the perspective of the health system. The study population comprised all seven-year-old children participating in the screening program in Shiraz. The present study dealt only with direct costs. The expected costs and outcomes, as well as the ICER index were estimated using the decision tree model. The study outcomes included averted disability-adjusted life years (DALY) and true identification of hearing loss cases. The robustness of the results was evaluated using the one-way sensitivity analysis. The TreeAge 2020 and Excel 2016 software were also used to analyze the collected data. Results The hearing screening data obtained during 6 years (2015-2020) showed that every year, an average of 22,853 children in Shiraz were examined for hearing, of which 260 were true positive (%1.1). The costs of screening and lack of screening were estimated at $30.32 Purchasing Power Parity (PPP) and $13.75 PPP per child, respectively. The averted DALY due to performing hearing screening was estimated at 7 years for each child. The ICER was positive and equal to $ 0.06 PPP for the identified cases and $ 2.37 PPP per averted DALY. The sensitivity analysis confirmed the robustness of the results. Conclusions According to the results, although hearing screening for primary school children had more costs and effectiveness, it was considered cost-effective. Therefore, universal screening with high quality and accuracy is recommended.